Direct Oxidative Dearomatization of Indoles with Aromatic Ketones: Rapid Access to 2,2-Disubstituted Indolin-3-ones - Liu, Jiarun; Huang, Jiancheng; Jia, Kuiyong; Du, Tianxing; Zhao, Changyin; Zhu, Rongxiu; Liu, Xigong (Synthesis, 2020)
A metal-free oxidative dearomatization of indoles with aromatic ketones mediated by TEMPO oxoammonium salt is described. The dearomatization proceeds smoothly and displays a broad substrate scope with respect to both indoles and aromatic ketones in the presence of H2SO4, affording the corresponding 2,2-disubstituted indolin-3-ones in good yields.
Keywords: indole; oxidative; dearomatization; aromatic ketone; 2,2-disubstituted indolin-3-one